Assessment and selection of fungal antagonists against Rhizoctonia solani - Grosch R; Faltin F; Lottmann J; Kofoet A; Berg G (浙江大学学报. 农业与生命科学版, 2004)
The soil-borne pathogen Rhizoctonia solani Kühn (teleomorph, Thanatephorus cucumeris [A. B. Frank] Donk) is worldwide responsible for serious damage of many economically important agricultural and horticultural crops. Control of Rhizoctonia diseases is difficult because this pathogen survives for many years as sclerotia in soil or as mycelium in organic matter under numerous environmental conditions. Furthermore, the pathogen has an extremely wide host range. To date, no effective control strategies against Rhizoctonia diseases are available in either organic farming or horticulture. In integrated pest management systems (IPM), mainly fungicides are used as control method. However, the European Union has decided that 60% of the chemical pesticides that were allowed in 1996 should be banned from 2003. Hence, new strategies to control one of the most important soil-borne pathogen R. solani are urgently needed. It is well-documented that an environmentally friendly alternative to protect plants against soil borne pathogens is biological control. Our work is concentrated on the development of a fungal biological control agent (BCA) especially selected against diseases caused by R. solani.Based on a combination of in vitro and in vivo assays 339 fungal plant-associated strains was evaluated against R. solani. The following characteristics were tested in vitro: antagonistic activity at 20 ℃and 12 ℃, the ability to produce cell wall-degrading enzymes (chitinase, β-1,3-glucanase, protease), and influence on sclerotia germination. The ability of spore production was also of importance under consideration of formulation of possible candidates. As results of the note characteristics six isolates were selected. Taxonomical characterization using molecular methods like BOX-PCR and sequencing of the 18S rDNA resulted in genetically diverse Trichoderma isolates. The disease suppression effect of the six fungal isolates were tested against bottom rot on lettuce and black scurf on potato in pot experiments in climate chamber. The conditions were favourable for the disease development by R. solani on both crops. All six isolates were able to suppress the disease severity on lettuce and potato. According to their biocontrol effect under field conditions the most efficient isolate will be commercialised as BCA product.